The lab book : situated practices in media studies - Wershler-Henry, Darren S. (Darren Sean), 1966-; Emerson, Lori; Parikka, Jussi, 1976- (University of Minnesota Press, 2021)
"An important new approach to the study of laboratories, presenting a practical method for understanding labs in all walks of life"--